Observed effects of the COVID-19 pandemic on the life satisfaction, psychological distress and loneliness of Australian carers and non-carers. (1st February 2022) - Abbasi-Shavazi, Azadeh; Biddle, Nicholas; Edwards, Ben; Jahromi, Maria
Abstract : Using six waves of longitudinal data, we investigate wellbeing, psychological distress and loneliness differences between informal carers and non-carers in the context of COVID-19-related policy changes in Australia. Wellbeing levels fluctuated along with the virus case numbers. Free childcare temporarily alleviated the disparity between carers and non-carers, but by its cessation, carers, in particular, reported lower wellbeing and higher psychological distress. Wage subsidies and income supports had opposing effects for carers' and non-carers' mental health but decreased the loneliness of both groups. Victorians, living in the state where the second wave of infections in Australia was concentrated, experienced worse outcomes than other Australians.